Digital and Sustainable Accounting for Corporate Value Creation - Renaldo, Nicholas (First Ciera Publisher, 2024)
This study examines the synergies between digital and sustainable accounting, emphasizing their combined potential in driving corporate value creation. The study adopts an exploratory case study approach to investigate the interplay between digital and sustainable accounting practices and their contribution to corporate value creation. This study uses purposive sampling, with criteria such as organizations are selected based on their adoption of digital and sustainable accounting practices and participants are chosen for their expertise and roles in implementing and managing these practices. This study used thematic analysis. The findings reveal that digital accounting tools streamline financial processes, enhance data accuracy, and facilitate real-time decision-making; sustainability integration in accounting aligns corporate strategies with environmental and social goals, strengthening stakeholder trust; a synergistic effect emerges when digital technologies enhance the implementation and reporting of sustainability practices, resulting in improved financial performance, operational efficiency, and brand reputation; and despite significant benefits, challenges such as high implementation costs, resistance to change, and data standardization persist, especially for smaller organizations.